2018
DOI: 10.1016/j.ygcen.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones and androgens differentially regulate gene expression in testes and ovaries of sexually mature Silurana tropicalis

Abstract: A series of ex vivo exposures using testicular and ovarian tissues of sexually mature Western clawed frogs (Silurana tropicalis) were designed to examine molecular mechanisms of thyroid hormone (TH) and androgen crosstalk sans hypophyseal feedback as well as investigate potential sex-specific differences. Tissues were exposed ex vivo to either triiodothyronine (T3), iopanoic acid (IOP), one co-treatment of IOP + 5α-dihydrotestosterone (5α-DHT), 5α-DHT, 5β-dihydrotestosterone (5β-DHT), or testosterone (T). Dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…In B. riojana, the testes begin to differentiate at mid‐prometamorphosis, regardless of absolute ages. This suggests that a minimum level of circulating thyroid hormone is a prerequisite for testicular development in this species (e.g., Wagner, Wajner & Maia, ; Campbell & Langlois, ; but see Duarte‐Guterman, Navarro‐Martin & Trudeau, ). Conversely, it is unclear why a certain absolute age must be reached for ovarian differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In B. riojana, the testes begin to differentiate at mid‐prometamorphosis, regardless of absolute ages. This suggests that a minimum level of circulating thyroid hormone is a prerequisite for testicular development in this species (e.g., Wagner, Wajner & Maia, ; Campbell & Langlois, ; but see Duarte‐Guterman, Navarro‐Martin & Trudeau, ). Conversely, it is unclear why a certain absolute age must be reached for ovarian differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown that the prevalence of thyroid disease in women was generally higher than that in men in various countries 25,26 . Animal experiments also showed that the thyroid of female animals responded more significantly to exogenous compound under the same exposure conditions 27,28 . Thyroid damage was more severe in females, so we only chose female offspring rats.…”
Section: Discussionmentioning
confidence: 99%
“…In in vitro studies, THs along with other gonadotropic hormones could inhibit the excessive production of androgens in theca cells isolated from medium-sized follicles ( 40 ). Animal studies have also reported that THs could decrease the expression of steroid 5α-reductase type 2, one androgen-related gene, playing anti-androgen effects in the ovary tissue of female S. tropicalis frogs ( 41 ). Another mechanism that affecting female AGD through estrogenic pathways has also been proposed ( 39 ).…”
Section: Discussionmentioning
confidence: 99%